Somatic mitochondrial mutation discovery using ultra-deep sequencing of the mitochondrial genome reveals spatial tumor heterogeneity in head and neck squamous cell carcinoma. (28th February 2020) - Schubert, Adrian D.; Channah Broner, Esther; Agrawal, Nishant; London, Nyall; Pearson, Alexander; Gupta, Anuj; Wali, Neha; Seiwert, Tanguy Y.; Wheelan, Sarah; Lingen, Mark; Macleod, Kay; Allen, Hailey; et al.
Abstract: Mutations in mitochondrial DNA (mtDNA) have been linked to risk, progression, and treatment response of head and neck squamous cell carcinoma (HNSCC). Due to their clonal nature and high copy number, mitochondrial mutations could serve as powerful molecular markers for detection of cancer cells in bodily fluids, surgical margins, biopsies and lymph node (LN) metastasis, especially at sites where tumor involvement is not histologically apparent. Despite a pressing need for high-throughput, cost-effective mtDNA mutation profiling system, current methods for library preparation are still imperfect for detection of low prevalence heteroplasmic mutations. To this end, we have designed an ultra-deep amplicon-based sequencing library preparation approach that covers the entire mitochondrial genome. We sequenced mtDNA in 28 HNSCCs, matched LNs, surgical margins and bodily fluids, and applied multiregional sequencing approach on 14 primary tumors. Our results demonstrate that this quick, sensitive and cost-efficient method allows obtaining a snapshot on the mitochondrial heterogeneity, and can be used for detection of low frequency tumor-associated mtDNA mutations in LNs, sputum and serum specimens. These findings provide the foundation for using mitochondrial sequencing for risk assessment, early detection, and tumor surveillance. Highlights: We develop an ultra-deep approach for sequencing of the mitochondrial genome. We sequenced 28 HNSCC tumors and matched lymph nodes, margins, blood and sputum. Clonal events were detected in patients with multi-regional sequencing. mtDNA content was increased in invasive tumor front section in a subset of patients. Tumor-specific mutations were detected in matched LNs, margins and bodily fluids.